Video Broadcast Courses at the Islamic Azad University Karaj Branch (Case Study) - Shahmohammadi, Nayereh (Mediterranean Journal of Social Sciences, 2012)
Distance educators are increasingly adopting both synchronous and asynchronous ICT-based modes ofcommunication to enhance distance learning environment. With the use of ICT-based modes, distancelearners are now able to participate in class in real time; interact with their lecturer and peers; and accesscourse and external information/resources at their own convenient time, place and pace.This paper seeksto assess the extent to which video broadcast enhances learning environment for distance learners at theIslamic Azad University Karaj Branch. Apart from print, video broadcast is also used as a delivery mode andmodes such as audio and video conferencing, and WebCT(tools) are used to supplement distance learning.This paper employs a multi-perspective evaluation design with survey questionnaires as the main andinterviews as the supplementary technique of data collection. Results suggest that video broadcast mode atIslamic Azad University Karaj Branch enriches the distance learning environment. ICT-based attributessuch as tele-presence, interaction and flexibility emerge as being enhanced by video broadcast mode.